A multicenter, non-interventional study to evaluate patient-reported experiences of living with psoriasis. (2nd January 2016) - Pariser, David; Schenkel, Brad; Carter, Chureen; Farahi, Kamyar; Brown, T. Michelle; Ellis, Charles N.; ,
Abstract: Background : Moderate to severe plaque psoriasis (with or without psoriatic arthritis) places significant burden on patients' lives. Objective : Explore and document patients' experiences of living with psoriasis, including symptoms, treatments, impact on daily lives and patient-reported functioning. Methods : In a US-based, non-interventional study, narrative interviews were conducted at baseline and again within 16 weeks. In interviews, patients with moderate to severe psoriasis indicated symptoms, ranked symptoms according to level of bother and indicated areas of their lives affected by psoriasis. Transcripts of interviews were coded for themes. Measurements of psoriasis severity including BSA, PGA and PASI were recorded. Results : Symptoms reported most frequently included flaking/scaling (non-scalp areas), itching/scratching and rash, while the most bothersome symptoms were itching/scratching, flaking/scaling (non-scalp areas) and skin pain. Frequently reported impact areas were social and emotional. Conclusion : Broad-reaching interviews with patients with psoriasis show that these patients suffer in many aspects of their lives and in ways not indicated by typical psoriasis severity measures. Patients with psoriatic arthritis reported symptoms and disease-related complications at higher rates than those without arthritis. Physicians' explorations of the effect of psoriasis on patients' life events could aid in managing these patients.